Executive compensation incentives and corporate performance: The moderating role of dual roles and governance insights - Qian, He; Sahari, Salawati Binti (International Journal of Management and Sustainability, 2025)
This study examines how executive compensation influences corporate performance, with a focus on the moderating effect of executives holding concurrent roles in shareholder units. Using 2023 data from 5,032 A-share listed firms in China and applying multiple linear regression with ROA as the performance metric, the results show a positive link between executive pay and performance. However, when dual roles exist, total management compensation negatively affects performance, suggesting agency issues arising from power concentration. In contrast, compensation for core executives (the top three earners) enhances performance, highlighting the value of targeted incentives. These findings underscore the need for differentiated compensation structures aligning general management pay with short-term goals and core executive rewards with long-term objectives. The study offers insights into optimizing governance and incentive design in China’s corporate sector.